Heterogeneity in COVID-19 infection among older persons in South Africa: Evidence from national surveillance data - Abdelatif, Nada; Naidoo, Inbarani; Dunn, Shanaaz; Mazinu, Mikateko; Essack, Zaynab; Groenewald, Candice; Maharaj, Pranitha; Msomi, Nokukhanya; Reddy, Tarylee; Roberts, Benjamin; Zuma, Khangelani (Frontiers in Public Health, 2023)
Background: The 2021 World Health Organisation study on the impact of COVID-19 on older people (≥60 years) in the African region highlighted the difficulties they faced as the virus spread across borders and dominated the way of life. These difficulties included disruptions to both essential health care services and social support, as well as disconnections from family and friends. Among those who contracted COVID-19, the risks of severe illness, complications, and mortality were highest among near-old and older persons. Objective: Recognising that older persons are a diverse group including younger- and older-aged individuals, a study was conducted to track the epidemic among near-old (50-59 years) and older persons (≥ 60 years) in South Africa covering the two years since the epidemic emerged. Methods: Using a quantitative secondary research approach, data for near-old and older persons were extracted for comparative purposes. COVID-19 surveillance outcomes (confirmed cases, hospitalisations, deaths) and vaccination data were compiled up to 5th March 2022. COVID-19 surveillance outcomes were plotted by epidemiological week and epidemic waves to visualize the overall growth and trajectory of the epidemic. Means for each age-group and by COVID-19 waves, together with age-specific rates, were calculated. Results: Average numbers of new COVID-19 confirmed cases and hospitalisations were highest among people aged 50-59- and 60-69-years. However, average age-specific infection rates showed that people aged 50-59 years and ≥ 80 years were most vulnerable to contracting COVID-19. Age-specific hospitalisation and death rates increased, with people aged ≥ 70 years most affected. The number of people vaccinated was slightly higher among people aged 50-59 years before Wave Three and during Wave Four, but higher among people aged ≥ 60 years during Wave Three. The findings suggest that uptake of vaccinations stagnated prior to and during Wave Four for both age groups. Discussion: Health promotion messages and COVID-19 epidemiological surveillance and monitoring are still needed, particularly for older persons living in congregate residential and care facilities. Prompt health-seeking should be encouraged, including testing and diagnosis as well as taking up vaccines and boosters, particularly for high-risk older persons.